2018
DOI: 10.17660/actahortic.2018.1204.27
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wetness duration, inoculum concentration and temperature on the development of Alternaria blight on transplants of sweet potato

Abstract: Alternaria blight (AB) of sweet potato caused by Alternaria bataticola is a limiting factor for sweet potato industries in various countries. The disease has been recently reported in South Africa. Thorough literature search indicates that factors influencing the development of AB have not been studied adequately. In the current study, wetness duration, inoculum concentration and temperature/wetness duration interaction were evaluated for their effects on the disease incidence and disease severity of AB of swe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Vloutoglou and Kalogerakis (2000) reported an increase from 2 to 88% leaf area infection by A. solani on tomato (Solanum lycopersicum L.) when the duration of leaf wetness was increased from 4 to 24 hours and no symptoms when wetness was less than 4 hours. Similarly, Kandolo et al (2018) reported temperature range of 20-25°C and wetness duration of 48 hours as the ideal conditions for the spread of Alternaria bataticola. Kachwekano had lower daily temperatures and higher relative humidity than Namulonge, consequently the residual moisture on the plants took longer to evaporate thereby facilitating the infection process.…”
Section: Discussionmentioning
confidence: 92%
“…Vloutoglou and Kalogerakis (2000) reported an increase from 2 to 88% leaf area infection by A. solani on tomato (Solanum lycopersicum L.) when the duration of leaf wetness was increased from 4 to 24 hours and no symptoms when wetness was less than 4 hours. Similarly, Kandolo et al (2018) reported temperature range of 20-25°C and wetness duration of 48 hours as the ideal conditions for the spread of Alternaria bataticola. Kachwekano had lower daily temperatures and higher relative humidity than Namulonge, consequently the residual moisture on the plants took longer to evaporate thereby facilitating the infection process.…”
Section: Discussionmentioning
confidence: 92%
“…Kandolo et al. (2018) found that the ideal conditions for spread of blight are 48 h of wetness and temperatures between 20°C and 25°C. Among the fungicides tested under field conditions, the mixture of azoxystrobin–difenoconazole at 375 mL/100 mL was the most effective in reducing Alternaria leaf and stem blight intensity (Kandolo et al., 2016).…”
Section: Research and Development Contributions Of The Arcmentioning
confidence: 99%